A comparative histological study of ceca and rectum in common kestrel (Falco tinnunculus) and white-eared bulbul (Pycnonotus leucotis) according to their food type: Iman mousa khaleal and Raghad jawad Salman - khaleal, Iman mousa (The Iraqi Journal of Veterinary Medicine, 2017)
The present study is designed to investigate the histological structure of large intestine of two species of Iraqi birds which belong to two different orders which vary in their kinds of food. Adult birds common kestrel (Falco tinnunculus) that belong to carnivorous and white-eared bulbul (Pycnonotus leucotis) which belongs to omnivorous. This study was carried on 10 birds (5 common kestrel and 5 white-eared bulbul) used for histological study of the ceca and rectum in the two species of birds that include the determination of ceca and rectum, measurements of height columnar cells, villus height, and the thickness of wall tunics. Different types of stains were used including Haematoxylin and Eosin as well as special stains including Periodic Acid Schiff, Alcian blue- Periodic Acid Schiff and Van Gieson. The present result revealed that the ceca was lymphoid type and the wall of the ceca consisted of mucosa, muscularis externa and serosa whereas the submucosa was absent in the two studied birds. The mucosa in ceca was formed by along villi, with different shapes at the proximal part of the ceca while in the middle parte it changed into folds or mounds like which were flat mucosa in the proximal part of the ceca in the two studied birds. The mucosa of ceca was lined by simple columnar cells with brush border and goblet cells; this epithelium extended to line the crypts of lieberkuhn in the bases of villi and folds. While the rectum appeared as muscular tube which consist of four basic of the digestive tract tunics; tunica mucosa, submucosa, muscularis externa and serosa. The mucosa was covered by simple columnar cells with brush border and numerous goblet cells that continue to line the crypts of lieberkuhn located between the villi and that which occupied the lamina propria.